Student Writers’ Affective Engagement with Grammar-Centred Written Corrective Feedback: The Impact of (Mis)Aligned Practices and Perceptions - Saeli, Hooman; Cheng, An (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2019)
This project firstly explored Iranian English as a foreign language (EFL) students’ perceptions about written corrective feedback (WCF)-related practices and preferences. Secondly, the student participants’ first language (L1; e.g., Farsi) learner identities were operationalized, especially focusing on the skill of writing, WCF, and grammar-centred WCF. Thirdly, the students’ affective engagement with WCF was scrutinized, particularly in light of L1 student identities. The participants in the study were 15 students in an Iranian EFL context. Analysis of interview data revealed that the skill of writing was held in low regard by the students. Also, several discrepancies emerged vis-à-vis WCF methods (e.g., direct vs. coded), error correctors (e.g., teacher feedback vs. peer feedback), the amount of correction (e.g., selective vs. comprehensive correction), and the relative importance of different components of writing (e.g., grammar vs. content vs. organization). In particular, the findings showed that the students’ L1 identities involved low regard for writing, but high regard for speaking skills, and that they attached high value to grammatical accuracy and teacher explicit feedback. Finally, the findings indicated that: (a) the students’ second language (L2) identities (e.g., WCF-related preferences) were profoundly affected by their L1 student identities, and (b) the discrepancies between the students’ L2 writing preferences (e.g., preferred amount of WCF) and the teachers’ reported practices could potentially hinder students’ affective engagement with WCF.